1989
DOI: 10.1111/j.1423-0410.1989.tb02017.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage of Whole Blood for up to 24 Hours at Ambient Temperature prior to Component Preparation

Abstract: The effect of rapid cooling to 20-24 degrees C of whole blood immediately after collection, using 'cooling units' with butane-1,4-diol and prolonged storage up to 24 h at ambient temperature was investigated in the whole blood and the subsequently prepared plasma, buffy coat and buffy-coat-poor red cell concentrate (BC-poor RCC) in saline-adenine-glucose-mannitol (SAG M) solution. Factor VIII:C content of the plasma (n = 10), after 24 h storage was 80 +/- 3% of the initial value. In routine procedures factor V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
179
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(199 citation statements)
references
References 19 publications
19
179
0
1
Order By: Relevance
“…If the unseparated whole blood is kept at ambient temperature, without active cooling, within several hours a clearcut decrease of 2,3–DPG can be observed, but even with active cooling less than 50% remains after 16–h [61]. Red cells stored in the most commonly used additive solutions have markedly decreased levels of 2,3–DPG after 1 week of storage and are often completely depleted after 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the unseparated whole blood is kept at ambient temperature, without active cooling, within several hours a clearcut decrease of 2,3–DPG can be observed, but even with active cooling less than 50% remains after 16–h [61]. Red cells stored in the most commonly used additive solutions have markedly decreased levels of 2,3–DPG after 1 week of storage and are often completely depleted after 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Pietersz et al [61]demonstrated the usefulness of heat–absorbing plates containing solid butane–1,4–diol which has a melting point at 20°C. If active cooling is not applied it will take about 6 h for a blood unit stored at ambient temperature to reach 25°C , with cooling plates it is reduced to about 2 h. The metabolic rate in the red cells is strongly influenced by temperature.…”
Section: Extended Hold Of Whole Blood Before Component Preparationmentioning
confidence: 99%
“…Mild alkalosis and a slight decrease in levels of organic phosphate in red blood cells could explain the OH-DC deviation. It has been previously shown that 2,3 DPG levels rapidly decrease in whole blood and packed red cells stored in CPD, CPDA-1 or CPDA-2 as anticoagulants (14,15,16,17) . In our study there was no important decrease in 2,3 DPG levels, even in patients whose lactate levels were very high.…”
Section: Discussionmentioning
confidence: 98%
“…These effects are also observed when whole blood is coooled down to 20 °C and stored at this temperature until separation [8]. However, the reduced citrate content increases Ca 2+ availability and thus the possible risk of activation of the coagulation or complement systems or other proteolytic activity.…”
Section: Introductionmentioning
confidence: 99%